Reviewing Literature in Bioethics Research: Increasing Rigour in Non-Systematic Reviews - McDougall, Rosalind (Bioethics, 2015)
The recent interest in systematic review methods in bioethics has highlighted the need for greater transparency in all literature review processes undertaken in bioethics projects. In this article, I articulate features of a good bioethics literature review that does not aim to be systematic, but rather to capture and analyse the key ideas relevant to a research question. I call this a critical interpretive literature review. I begin by sketching and comparing three different types of literature review conducted in bioethics scholarship. Then, drawing on Dixon-Wood's concept of critical interpretive synthesis, I put forward six features of a good critical interpretive literature review in bioethics: answering a research question, capturing the key ideas relevant to the research question, analysing the literature as a whole, generating theory, not excluding papers based on rigid quality assessment criteria, and reporting the search strategy.